2021
DOI: 10.1038/s41598-021-93063-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new GLUT2-selective inhibitors through in silico ligand screening and validation in eukaryotic expression systems

Abstract: Glucose is an essential energy source for cells. In humans, its passive diffusion through the cell membrane is facilitated by members of the glucose transporter family (GLUT, SLC2 gene family). GLUT2 transports both glucose and fructose with low affinity and plays a critical role in glucose sensing mechanisms. Alterations in the function or expression of GLUT2 are involved in the Fanconi–Bickel syndrome, diabetes, and cancer. Distinguishing GLUT2 transport in tissues where other GLUTs coexist is challenging du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…Virtual screening involves computational estimation of the optimal binding of a library of potential drugs against targets of interest. This procedure can greatly reduce the time and cost of the drug development compared to in vitro screening alone and has been frequently used to identify compounds with therapeutic potential [21] , [22] , [23] , [24] , [25] . Natural compounds are a valuable source of molecules for drug screening.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual screening involves computational estimation of the optimal binding of a library of potential drugs against targets of interest. This procedure can greatly reduce the time and cost of the drug development compared to in vitro screening alone and has been frequently used to identify compounds with therapeutic potential [21] , [22] , [23] , [24] , [25] . Natural compounds are a valuable source of molecules for drug screening.…”
Section: Introductionmentioning
confidence: 99%
“…However, functional studies on the GLUT2∆loopS_Q455R variant in yeast revealed similar substrate specificities and affinities as those of the WT transporter (Schmidl et al, 2021c). Presumably, the large extracellular loop mediates a correct folding and protein trafficking to the membrane in human cells but impedes the same processes in yeast due to differences in the membrane composition and/or signaling reactions.…”
Section: 11mentioning
confidence: 97%
“…screening (Schmidl et al, 2021c), revealing the demand for an additional, subsequent investigation platform. Requirements for such a system are high.…”
Section: Systems For Assaying Glut Activity and Identifying Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations